PENGARUH PERILAKU KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. INDONESIA POWER - PLTU JERANJANG LOMBOK - Borsalino, Melky Victor; Surati, Surati; Wahyulina, Sri (Jurnal Magister Manajemen, 2021)
This study aims to determine the effect of leadership behavior and organizational culture on the performance of employees of PT Indonesia Power-PLTU Jeranjang OMU. The population in this study were all organic employees from the executive level to the executive who worked at PT Indonesia Power - PLTU Jeranjang OMU. The findings of this study are that leadership behavior has a positive and significant effect on performance, and organizational culture also has a positive and significant effect on the performance of employees of PT Indonesia Power - PLTU Jeranjang OMU.